2001
DOI: 10.1007/s007870170038
|View full text |Cite
|
Sign up to set email alerts
|

Smoking in relation to psychosocial risk factors in adolescents

Abstract: Smoking behaviour in adolescence may be part of a pattern of problematic behaviour and may be linked to various psychopathological disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
21
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 0 publications
6
21
1
3
Order By: Relevance
“…In our population, living with both parents was protective for both gender groups. Previous studies have shown a reduced likelihood of smoking among adolescents who exercised [36]. However, no relationship was found between extracurricular sports and smoking in our study.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…In our population, living with both parents was protective for both gender groups. Previous studies have shown a reduced likelihood of smoking among adolescents who exercised [36]. However, no relationship was found between extracurricular sports and smoking in our study.…”
Section: Discussioncontrasting
confidence: 95%
“…Recent statistics published in 2005 by the "Observatoire Français des drogues et desagency dedicated to the fight against addictions), indicated that the proportion of daily tobacco smokers was decreasing with age for both sexes but was the highest in young adults (25-34 years 40% for men and 30% for women) [24]. Accordingly, in the same report, high dependency to tobacco smoking was shown to increase with age up to 44 years (from 11% for the 18-25 to 23% for the [36][37][38][39][40][41][42][43][44]. These statistics, prompted us to analyse unpublished data collected in '93-'94 for sex and gender differences in relation to tobacco smoking in a representative sample of 14,278 students aged 8 to 25 attending French public secondary schools.…”
Section: Introductionmentioning
confidence: 97%
“…These include the difficulties in using standardised international methodologies for assessing tobacco use (18,19). It is possible that under-reporting of severity of this addiction may have occurred because of negative associations with the habit (28). Also, although the study maintained strict anonymity of the respondents, female students needed some reassurance before they agreed to participate.…”
Section: Discussionmentioning
confidence: 99%
“…Tomori et al (2001) highlighted the importance of conflict within the family, pointing out that smoking in adolescence is more likely in settings in which family conflict is more frequent, and in which there is a lack of emotional support from the parents. Hetherington et al (1998) argued that dysfunctional family relations, such as conflict, negativity, lack of support and non-authoritative parenting practices, exacerbated the effects of divorce and remarriage on the children's adjustment.…”
Section: Discussionmentioning
confidence: 99%